STUDI KASUS ASUHAN KEPERAWATAN PADA PASIEN DENGAN STROKE NON HEMORAGIK DI RUMAH SAKIT HERMINA BEKASI - Ening Wahyuni; Indriyani Darmawan; Ria Anugrahwati (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2023)
Non-Hemorrhagic Stroke is a stroke caused by a blockage of blood vessels in the brain by thrombosis or embolism so that the supply of glucose and oxygen to the brain is reduced. A person who experiences a non-haemorrhagic stroke can experience dizziness, hemiplegia, and swallowing disorders. Through nursing care, stroke patients are carried out monitoring the patient's level of consciousness, training muscle strength, and helping to fulfill daily life. The purpose of this case study was to find out the description of nursing care for stroke patients in inpatient rooms. This case study is descriptive oriented to the nursing process approach method. This case study activity was carried out on March 28 - 30 2022 in the Hospital Inpatient Room. Hermina Bekasi. The subject of this case is Mrs. G with a diagnosis of Non Haemorrhagic Stroke. The results of the case study show that the management of nursing care in nursing problems with cerebral tissue perfusion disorders, characterized by dizziness and increased blood pressure of 160/90 mmHg. Nursing problems that have been resolved include: impaired cerebral tissue perfusion and impaired physical mobility. The unresolved nursing problem is swallowing disorder, because the patient cannot swallow and is still using an NGT. Actions taken by nurses include: monitoring the level of consciousness, vital signs, giving semi-Fowler's position, ROM and involving the family in carrying out simple mobilizations. Recommendations for nursing actions in providing semi-Fowler's position and effective ROM to improve the recovery of stroke patients.